COMPARATIVE CHARACTERISTICS OF TREATMENT METHODS FOR PATIENTS WITH ODONTOGENIC PHLEGMONS - A.V. Kiptiliy (Український стоматологічний альманах, 2023)
Optimizing the treatment of purulent-inflammatory diseases of the maxillofacial area is one of the urgent tasks of maxillofacial surgery, this is due to a number of objective reasons, which include changes both on the part of the macroorganism and on the part of inflammatory agents. The purpose of the study was to search and analyze scientific sources in Ukraine and the world, regarding the latest methods of treatment of odontogenic phlegmon, features of their course and complications.